2021
DOI: 10.1021/acs.est.0c08162
|View full text |Cite
|
Sign up to set email alerts
|

Porewater Lead Concentrations Limited by Particulate Organic Matter Coupled With Ephemeral Iron(III) and Sulfide Phases during Redox Cycles Within Contaminated Floodplain Soils

Abstract: Lead contamination in soils and sediments is a major threat to water quality. In surface and near-surface environments, Pb is not redox active; however, common Pb hosts, including Fe(III)-(hydr)oxides and sulfides, dissolve and precipitate as redox conditions change. Dissolution of Pb hosts may release Pb to porewater, leading to spikes in dissolved Pb concentrations and potential transport into surface or groundwater. Here, we examine the impacts of hydrologically coupled redox transitions on Pb partitioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 32 publications
3
28
0
Order By: Relevance
“…These could include sulfide species, manganese species, and/or quinone functional groups in organic matter. Mackinawite was observed at this field site, 34 and its presence is consistent with a rise in total sulfur concentrations around 150 cm (Figure 1d). Dewey et al 34 further observed elevated concentrations of reduced organic sulfur and elemental sulfur at this depth based on results from sulfur X-ray absorption spectroscopy, which was consistent with sulfide formation during microbial sulfate reduction.…”
Section: Rate and Rank Correlationsupporting
confidence: 75%
“…These could include sulfide species, manganese species, and/or quinone functional groups in organic matter. Mackinawite was observed at this field site, 34 and its presence is consistent with a rise in total sulfur concentrations around 150 cm (Figure 1d). Dewey et al 34 further observed elevated concentrations of reduced organic sulfur and elemental sulfur at this depth based on results from sulfur X-ray absorption spectroscopy, which was consistent with sulfide formation during microbial sulfate reduction.…”
Section: Rate and Rank Correlationsupporting
confidence: 75%
“…Previous studies reported mackinawite (FeS) in a similar column system with Wind River fines 4 and in Slate River field samples. 46 Consistent with the formation of Fe sulfides, total S concentrations followed similar trends as total Fe(II) concentrations across the columns (Figure S13) and aqueous sulfide concentrations were close to or below the detection limit in all ports throughout the experiment (Figure S5).…”
Section: Environmental Science and Technologysupporting
confidence: 62%
“…Wind River fines are exposed to high sulfate levels in the field and, thus, contain a high abundance of sulfate-reducing microorganisms, 45 whereas Slate River fines are exposed to lower sulfate concentrations and have greater Fe(II) levels. 46 In the sand of both Wind River and Slate River columns, Fe(II) concentrations initially increased downstream of the lenses and remained stable at these elevated concentrations 21 d into the experiment. Measured Fe(II) concentrations in the ports located 3 to 6 cm downstream of the Wind River lenses (at 10.5 and 13.5 cm) were 14-fold higher at the end of the experiment than Fe(II) concentrations that we simulated using a model incorporating only transport of Fe(II) out of the lenses but no microbial or chemical reactions (Figure 1d,g).…”
Section: ■ Results and Discussionmentioning
confidence: 91%
See 2 more Smart Citations